Increased phosphorylation of Cx36 gap junctions in the AII amacrine cells of RD retina - Ivanova, Elena; Yee, Christopher W.; Sagdullaev, Botir T. (Frontiers in Cellular Neuroscience, 2015)
Retinal degeneration (RD) encompasses a family of diseases that lead to photoreceptor death and visual impairment. Visual decline due to photoreceptor cell loss is further compromised by emerging spontaneous hyperactivity in inner retinal cells. This aberrant activity acts as a barrier to signals from the remaining photoreceptors, hindering therapeutic strategies to restore light sensitivity in RD. Gap junctions, particularly those expressed in AII amacrine cells, have been shown to be integral to the generation of aberrant activity. It is unclear whether gap junction expression and coupling are altered in RD. To test this, we evaluated the expression and phosphorylation state of connexin36 (Cx36), the gap junction subunit predominantly expressed in AII amacrine cells, in two mouse models of RD, rd10 (slow degeneration) and rd1 (fast degeneration). Using Ser293-P antibody, which recognizes a phosphorylated form of connexin36, we found that phosphorylation of connexin36 in both slow and fast RD models was significantly greater than in wildtype controls. This elevated phosphorylation may underlie the increased gap junction coupling of AII amacrine cells exhibited by RD retina.